A New Residual Convolutional Neural Network-Based Speech Improvement (International Journal of Innovative Research in Computer Science & Technology, 2022)
Among the most crucial methods for  denoising a noisy voice signal and enhancing its quality is  speech enhancement. This study makes use of Adaptive  Residual Neural Network technique to reduces maximum off  background noise. This method continuously monitors the  background noise depends upon the environmental changes  using SNR parameter. It has two functions first one is non  linear functions followed by convolutional neural networks  and second one is linearity followed due to Residual neural  networks. By using these factors remove background noise  even SNR is low conditions. Compared to other techniques this  technique is new,fastest, requires less training and also reduces  size.
Keywords: Convolutional Neural Networks; Liver; Segmentation; Tumor; ResNet; Deep Learning